Empowering Santri to Create Sustainable Economy at Pondok Pesantren Munzalan Mubaroka Siliragung Banyuwangi through Asset-Based Community Development (ABCD) - Nurul Inayah; Lely Ana Ferawati Ekaningsih; M. Alaika Nasrulloh (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Eco-Islamic boarding schools or green Islamic boarding schools are efforts to provide a "green" label for Islamic boarding schools that have a contribution to environmental and natural conservation. Assistance for students at the Munzalan Mubarokah Islamic Boarding School in realizing eco-Islamic boarding schools is carried out with two programs, namely the land use program and the waste and garbage program. The method used in this assistance uses the ABCD approach method. The results of the assistance of the santri to create an eco-Islamic boarding school are as follows: the first activity is to use the land to become a vegetable garden, namely leek and strawberry plants. This activity went well and was implemented by 90%. The second activity of chicken coop renovation has been carried out 100%. The third activity is sorting organic and inorganic waste and making trash bins. The activities of sorting organic and inorganic waste can already be carried out by students, although some are still not used to it. It can be said that this activity has been carried out by 80%, while the activity of making trash cans has been carried out 100%. And the fourth activity is the eco-Islamic boarding school development book, which can be said to have been implemented 80%. So that it can be said that in general the assistance of santri in realizing this eco-Islamic boarding school has been carried out by 90% with all the support and also obstacles during this assistance activity. Keywords: Santri Assistance, Eco-Islamic Boarding School, Environment, Green Islamic Boarding School